2012
DOI: 10.4103/0970-0358.105959
|View full text |Cite
|
Sign up to set email alerts
|

CT angiographic evaluation of perforators in the lower limb and their reconstructive implication

Abstract: Background:The perforator flaps evolved on the knowledge of the vascular tree from the main vascular trunk up to the subdermal plexus. Therefore, we thought that it's necessary to map the whole vascular arcade by CT angiography. The aim of this study is to evaluate the perforators and the whole vascular tree of the lower limb by peripheral CT angiography with 3D reconstruction and intraoperative evaluation. This study helps in designing flaps of different constituents based on the selected perforators.Material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…Thus, studies in these patients are needed. Although the validity of US for detection of perforators has been confirmed in previous reports, 16,17 inter-and intraobserver reliability was not evaluated, which is a major limitation of the present study. While using a high-frequency transducer, it is difficult to find deep perforators in the proximal forearm and smaller perforators that are less than 0.2 mm in diameter.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Thus, studies in these patients are needed. Although the validity of US for detection of perforators has been confirmed in previous reports, 16,17 inter-and intraobserver reliability was not evaluated, which is a major limitation of the present study. While using a high-frequency transducer, it is difficult to find deep perforators in the proximal forearm and smaller perforators that are less than 0.2 mm in diameter.…”
Section: Discussionmentioning
confidence: 61%
“…2 In an attempt to enhance the preoperative delineation of perforators, several approaches such as angiography, CTA, DSA, MRA, and color Doppler US have already been applied. 3,[14][15][16] Color Doppler US is noninvasive, without radiation exposure; the equipment is small in size and conveniently portable, and the examination procedure is rapid, low cost, and easy to perform. In 1994, Rand et al reported the first assessment of the inferior epigastric artery perforators for transverse rectus abdominis myocutaneous flap using color Doppler US, which improved the surgeon's ability to design and elevate a flap.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, dynamic multi-slice 3D CT angiography has revolutionized many surgical fields [ 2 ]. 3D reconstruction with volume rendering technique using images of the delayed phase of peripheral CT angiography provided most clear delineation of the peripheral venous arcade.…”
Section: Discussionmentioning
confidence: 99%
“…They recommended preoperative duplex scanning to assess and map the location of the SSV. Recently, dynamic multi-slice three-dimensional (3D) computed tomography (CT) angiography has been used in many surgical fields [ 2 ]. Especially, a 3D CT volume rendering technique is a possible noninvasive method for the diagnosis of unusual lower extremity varicose veins [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in areas where there is thicker fat tissue, computed tomographic angiography can provide a clearer perforator image, including its origin, position, intramuscular and subcutaneous course, and relationship with the trunk vessel [20][21][22][23] ; however, in areas where there is limited fat tissue, computed tomographic angiography is not as clear. Although the blood flow signal detected by color Doppler ultrasound in the deeper tissue layers is not clear because of the intermittent image capture, 18,24-26 color Doppler ultrasound is very sensitive to the perforators in the superficial tissue planes, where the hemodynamic signal is easier to detect.…”
Section: Cta (%) Cdu (%) Cta (%) Cdu (%)mentioning
confidence: 99%